Analysis of Hotel Tax Policy as an Instrument for Tax Collection on Homestays in Tourism Villages - Diani Widiastuti; Inayati Inayati (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Determination of hotel tax policy as an instrument of tax collection on tourist village homestays is important in developing the tourism sector in Indonesia, but in its implementation the determination of hotel tax as an instrument of tax collection on tourist village homestays does not fulfill the principle of equality in the context of equality. This study aims to analyze the principle of justice (equality) for the regulation of hotel tax as an instrument for collecting tourism village homestay taxes by using the concept of equity (equality). This research was conducted using a qualitative approach and data was collected by reviewing the literature from various related sources. The results of the study show that based on 2 (two) measurements drawn from the concept of justice (equality), the first is based on the similarity of circumstances, does not yet reflect justice where the criteria for a tourist village homestay are different from other types of lodging, so there is a need for adjustments to the definition of a tourist village homestay. Furthermore, based on non-discrimination, the government still thinks that a tourism village homestay provider is someone who is qualified in their field, so a rate adjustment is needed so that fairness in hotel tax collection for tourism village homestays can be achieved.